Research on using mineral sorbents for a sorption process in the environment contaminated with petroleum substances = Badanie procesu sorpcji skażeń środowiska substancjami ropopochodnymi z wykorzystaniem sorbentów mineralnych - Pijarowski, Piotr Marek; Tic, Wilhelm Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A research on diatomite sorbents was carried out to investigate their ability to remove hazardous substances from oil spillages. We used two types of sorbents available on the market with differences in material density and particles size of composition. As sorbents we used Ekoterm oil and unleaded petrol 95 coming from refinery PKN Orlen S.A.
Keywords: sorbenty; sorbenty mineralne; substancje ropopochodne; sorbents; mineral sorbents